Determinants of Banks Profitability & Liquidity and the Role of BASEL III in Islamic & Conventional Banking Sector of Pakistan: A Case Study of NBP - Bibi, Sitara; Mazhar, Fatima (The Economics and Finance Letters, 2019)
This study aimed to examine and compare the performance of Islamic and Conventional banking sector of Pakistan in terms of the impact of BASEL III reforms on the profitability and liquidity of Islamic and conventional banks of Pakistan. For this purpose, National bank of Pakistan has been taken as a unit of analysis and eight year’s financial data has been collected from the official website of NBP. BASEL III standard’s ratios including CAR, CER and LCR have been used as an independent variable while the bank’s profitability and liquidity have been taken as a dependent variable. Descriptive statistics have been performed first to examine and compare the performance of both Islamic and conventional banking sector before and after the induction of BASEL III. After that T-Test has been performed to investigate the differences between the impact of BASEL III on the profitability and liquidity of Islamic and conventional banking sector. The regression analysis has been performed to examine whether BASEL III has a strong relationship with Islamic or conventional banking sector. The results found that BASEL III has a significant positive relationship with the profitability and liquidity of the Islamic sector. Islamic banks are higher in terms of the impact of BASEL III on profitability and liquidity. They are more profitable, more liquid and highly capitalized with BASEL III standards. While Conventional banking sector needs to redesign their policies and make them more compliant with BASEL III to generate more profit and be more liquid as Islamic banks are.